An experimental study comparing the role played by the ‘pre-experience’ and the ‘post-experience’ phases in respect with ‘perception’ and ‘memory’ to test the practical application of Perception Experience Memory Model of advertising. - Ghiya, Krishn/ KG (2015)
This study aims to bridge the gap between the theoretical and practical applications between the theories of advertising. After comparing and contrasting the Elaboration Likelihood Model (ELM) (Petty, et al., 1983), the Information Processing Model (Engel, et al., 1993) and the Perception Experience Memory (PEM) model (Hall, 2002) of advertising, the research became more focussed towards the PEM model. Although, this relatively newer theory is a combination of merits of the ELM and the IPM, it is still not popular which made it imperative to unveil the reasons behind the “academician-practitioner gap” (Hunt, 2002, p. 305). This was achieved by exploring the role played by the pre-experience (before the usage of a product) and the post-experience (after the usage of a product) phases in determining the ‘framing of perception’ and ‘memory’ within the mind-set of consumers. This was carried out by conducting a marketing experiment by showing the Sony PlayStation 4 advertisement, followed by a questionnaire to measure the appropriate responses across the pre-experienced and the post-experienced group. The differences in the perception and memory of the participants between the two groups were recorded by analysing the questionnaires using the quantitative research techniques via individual sample t-tests. It was discovered that the theoretical aspects of the PEM model were justified and product experience had a positive impact on perception and memory of the consumers. It was also determined that the speed of processing the advertisement was higher in the post-experienced group than the pre-experienced group. However, in the case of well established brand/product such as Sony PlayStation 4, even the pre-experience leads to the function of ‘organizing memory’ which suggests that the addition of another loop should take place connecting the pre-experience exposure to the function of ‘organizing memory’. These two additions of adding a ‘time-frame’ and an additional loop would significantly reduce the “academician-practitioner gap” (Hunt, 2002, p. 305) by enhancing the accuracy and would lead to advancement in the field of advertising theory.